Diabetes Care in India - Shashank R. Joshi (Ubiquity Press, 2016)
Background: Diabetes has become a major health care problem in India with an estimated 66.8 million people suffering from the condition, representing the largest number of any country in the world. Objective: The rising burden of diabetes has greatly affected the health care sector and economy in India. The goal of health care experts in India is to transform India into a diabetes care capital in the world. Methods: An expert detailed review of the medical literature with an Asian Indian context was performed. Findings: Recent epidemiologic studies from India point to a great burden from diabetes. Diabetes control in India is far from ideal with a mean hemoglobin A1c of 9.0%-at least 2.0% higher than suggested by international bodies. Nearly half of people with diabetes remain undetected, accounting for complications at the time of diagnosis. Screening can differentiate an asymptomatic individual at high risk from one at low risk for diabetes. Despite the large number of people with diabetes in India, awareness is low and needs to be addressed. Other challenges include balancing the need for glycemic control with risk reduction due to overly tight control, especially in high-risk groups and taking into account health care professional expertise, attitudes, and perceptions. Pharmacologic care should be individualized with early consideration of combination therapy. Regular exercise, yoga, mindful eating, and stress management form a cornerstone in the management of diabetes. Conclusions: Considering the high cost incurred at various steps of screening, diagnosis, monitoring, and management, it is important to realize the cost-effective measures of diabetes care that are necessary to implement. Result-oriented organized programs involving patient education, as well as updating the medical fraternity on various developments in the management of diabetes, are required to combat the current diabetes epidemic in India.